2014
DOI: 10.1111/tct.12158
|View full text |Cite
|
Sign up to set email alerts
|

Online assessment: what influences students to engage with feedback?

Abstract: This research found that feedback provided through an online marking tool overcame many of the problems associated with handwritten feedback, but alone was not enough to ensure universal engagement. Feedback dialogues are proposed as a method to overcome negative student experiences, enhance tutor performance and encourage future student engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 10 publications
2
11
0
7
Order By: Relevance
“…In contrast to our study, Ada and Stansfield () found that gender was unrelated to feedback access. Likewise, our results also suggest that “feedback collection” rates in the LMS can be quite low, while previous studies have indicated relatively high access to feedback files (Ada & Stansfield, ; Stone, ; Zimbardi et al , ). Most of the LMS used in these studies allow for the simultaneous viewing of marks and feedback within a single web interface, as opposed to our study where feedback files had to be downloaded.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In contrast to our study, Ada and Stansfield () found that gender was unrelated to feedback access. Likewise, our results also suggest that “feedback collection” rates in the LMS can be quite low, while previous studies have indicated relatively high access to feedback files (Ada & Stansfield, ; Stone, ; Zimbardi et al , ). Most of the LMS used in these studies allow for the simultaneous viewing of marks and feedback within a single web interface, as opposed to our study where feedback files had to be downloaded.…”
Section: Discussionsupporting
confidence: 68%
“…Most students indicate that they read feedback comments when surveyed (97%—Higgins, Hartley, & Skelton, ; 87%—Doan, , 100%—Stone, ) and within LMS, results so far have indicated high engagement with feedback when marks and feedback were presented simultaneously (Stone, ; Zimbardi et al , ). In contrast, our analysis of access logs for over 1400 individual pieces of assessment feedback revealed that when marks are reported first, and feedback files must be downloaded separately, many students may not even attempt to access feedback files.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the nature of written feedback as being perceived as a one-way (Stone 9 ) experience from instructor-to-student, even though the act of reading is required to complete the feedback loop. As with other research studies, Stone 9 confirms the ongoing rhetoric surrounding feedback methods in online courses in that it is necessary and more than often, welcomed by students who are generally open to the experience.…”
Section: Feedback To Improve Students' Perception Of Engagementsupporting
confidence: 77%
“…surveys improved the quality and quantity of feedback to the students, while also improving the perceived quality of the clerkship. [11][12][13] Among these, the formative value of electronic feedback methods varied, or in some instances, was not measured. One study using quick response (QR) technology in a surgical residency program demonstrated increased longitudinal postprocedure feedback resulting in high feedback quality satisfaction rates.…”
Section: Discussionmentioning
confidence: 99%